2019
DOI: 10.1007/s00264-019-04307-z
|View full text |Cite
|
Sign up to set email alerts
|

Autologous mesenchymal stem cell implantation, hydroxyapatite, bone morphogenetic protein-2, and internal fixation for treating critical-sized defects: a translational study

Abstract: Introduction Critical-sized defect (CSD) is one of the most challenging cases for orthopaedic surgeons. We aim to explore the therapeutic potential of the combination of bone marrow-derived mesenchymal stem cells (BM-MSCs), hydroxyapatite (HA) granules, bone morphogenetic protein-2 (BMP-2), and internal fixation for treating CSDs. Methods This was a translational study performed during the period of January 2012 to 2016. Subjects were patients diagnosed with CSDs who ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…The combined approach of osteoconductive scaffolds and osteoinductive growth factors may have synergistic effects on osteogenesis ( 17 ). In a previous report, the application of a combined approach with bone marrow mesenchymal stem cells, BMP-2 and hydroxyapatite led to successful treatment of critical-sized defects in human beings ( 18 ). Bone marrow stem cells were loaded into a hydrogel system by enzyme-catalyzed crosslinking, and the addition of bone BMP-2 led to the improvement of osteogenic potential ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…The combined approach of osteoconductive scaffolds and osteoinductive growth factors may have synergistic effects on osteogenesis ( 17 ). In a previous report, the application of a combined approach with bone marrow mesenchymal stem cells, BMP-2 and hydroxyapatite led to successful treatment of critical-sized defects in human beings ( 18 ). Bone marrow stem cells were loaded into a hydrogel system by enzyme-catalyzed crosslinking, and the addition of bone BMP-2 led to the improvement of osteogenic potential ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…The first approach is considered a 'top-down' approach, whereby bioengineering focus is placed on optimising the extracellular environment to augment MSC differentiation down. Success has been demonstrated by including the combination of MSCs with hydroxyapatite (HA) granules and bone morphogenetic protein-2 (BMP-2), to promote osseointegration by utilising the biocompatibility and porosity of the added materials [32,38]. Dilogo et al appear to have demonstrated effective clinical results in promoting fracture healing and scaffold integration by utilising MSC and a 'top-down' approach in treating segmental bone defects in the non-union setting, utilising MSCs, HA granules and BMP-2 to facilitate both an osteogenic and osteoinductive environment [38].…”
Section: Preparation and Conditioning Of Mscsmentioning
confidence: 99%
“…The first approach is considered a ‘top-down’ approach, whereby bioengineering focus is placed on optimising the extracellular environment to augment MSC differentiation down. Success has been demonstrated by including the combination of MSCs with hydroxyapatite (HA) granules and bone morphogenetic protein-2 (BMP-2), to promote osseointegration by utilising the biocompatibility and porosity of the added materials [ 32 , 38 ]. Dilogo et al.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations